Development of International Clusters in the Baltic Sea Region - Mikhailov Andrei (Baltic Region, 2013)
This article offers a comprehensive definition of international, cross-border, and transnational clusters. The author presents a classification of international clusters of the Baltic Sea states, and identifies cross-border and transnational clusters. The paper considers the features of international clusters in the Baltic Sea region, as well as certain cases of implementation of national and international cluster policy. A comparative analysis of the Baltic Sea region provides a basis for identifying countries with high concentration of international clusters such as the Scandinavian countries and Germany. Also, the analysis indicates the potential participants of international clusters, namely the Baltics and Poland as they are involved in a large number of international cluster initiatives. The author identifies the factors contributing to the formation of international clusters in the Baltic Sea region.